Effect of Binaural Masking Noise on Stuttering - A Spectographic, Analysis - VU, Nandur (Journal of All India Institute of Speech and Hearing)
The present study was aimed at spectrographically analysing the different parameters of speech i.e., fundamental frequency of voice, vocal level, vowel duration and voice onset time of stutterers and non-stutterers in the absence and in the presence of binaural masking noise in reading condition. In addition, the effect of noise on rate of speech and frequency of stuttering were also observed.